Application of Ionic Liquids ss Reaction Media for The Xylanase Reaction - Ika Oktavianawati (Jurnal ILMU DASAR, 2011)
The potential for performing Thermomyces lanuginosus xylanase-catalyzed reactions on birchwood xylan dissolved in a range of ionic liquids has been investigated. As apparent from the results, some of the selected hydrophobic ionic liquids performed as better facilitators of the hydrolysis reactions than the hydrophilic ones. Thus, the xylanase reaction profiles in these hydrophobic ionic liquids, including [Py1,4]tfsa, [C4MIm]PF6, [P6,6,6,14]BF4, [P6,6,6,14]dca, [P6,6,6,14]bisphosphinate, and [C1MIm]MeSO4, were investigated in greater detail and the conditions for optimum temperature, optimum pH, and kinetic parameters documented. [P6,6,6,14]bisphosphinate was found to be the best ionic liquid producing the highest xylanase activity (84.98 unit/mg protein) at high temperature and pH, namely at 85°C and pH 9.0, respectively, among all of the ionic liquids tested. In addition, this ionic liquid increases the specificity of the xylanase toward xylan, indicated by lower KM (6.42 mg/mL), though it does not observed well on its enzyme’s enhancement rate. Therefore, this study indicates that the application of this ionic liquid for the hydrolysis of real lignocellulosic samples, such as wood pulp, is warranted. Further investigations, outside the scope of this research will be required to validate these observations.